Evolution and Research Trends in Physical Culture. A Longitudinal Analysis of Student Diploma Theses from the Didactic Team of Physical Culture Sciences, formerly the Department of Physical Culture, Faculty of Earth Sciences and Spatial Management, 2017-2024 - Magdalena Hagner-Derengowska; Anna Michalska; Radosław Muszkieta; Olga Smoleńska; Walery Zukow (Journal of Education, Health and Sport)
Objective: The aim of this study was to conduct a comprehensive analysis of diploma theses produced in the Department of Physical Culture at the Faculty of Earth Sciences and Spatial Management between 2017-2024, to identify main research trends, thematic evolution, and assess the impact of external factors on research directions in the field of physical culture.